2015
DOI: 10.1515/pac-2014-1006
|View full text |Cite
|
Sign up to set email alerts
|

Carbaboranes – more than just phenyl mimetics

Abstract: Dicarba-closo-dodecaboranes(12) (C2B10H12, carbaboranes) are highly hydrophobic and stable icosahedral carbon-containing boron clusters. The cage framework of these clusters can be modified with a variety of substituents, both at the carbon and at the boron atoms. Substituted carbaboranes are of interest in medicine as boron neutron capture therapy (BNCT) agents or as pharmacophores. High and selective accumulation in tumour cells is an important requirement for a BNCT agent and is achieved by incorporating bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…highly stable peptide bond between the carboxylic acid of boron-rich derivatives and an amino group of the biomolecule of interest (e.g. lysine in specific peptides) is a much-favoured coupling strategy 20,48,[50][51][52][53] and was also employed here for the thioglycolic acid derivative 4. Compound 4 could be incorporated up to three times into the breast cancer-selective peptide [F 7 ,P 34 ]-NPY at positions 4, 18 and 22.…”
Section: Peptide Conjugates and Biochemical Evaluationmentioning
confidence: 99%
“…highly stable peptide bond between the carboxylic acid of boron-rich derivatives and an amino group of the biomolecule of interest (e.g. lysine in specific peptides) is a much-favoured coupling strategy 20,48,[50][51][52][53] and was also employed here for the thioglycolic acid derivative 4. Compound 4 could be incorporated up to three times into the breast cancer-selective peptide [F 7 ,P 34 ]-NPY at positions 4, 18 and 22.…”
Section: Peptide Conjugates and Biochemical Evaluationmentioning
confidence: 99%
“…[29,[32][33][34] Since the volume of carboranes is slightly larger than a rotating benzene ring, they can be described as three-dimensional benzene analogues. [28,35] Besides their hydrophobic nature, which is beneficial for enhanced cell membrane penetration, multiple noncovalent interactions, like dihydrogen bond formation, may increase the affinity to biological targets, including enzymes or receptor proteins. [27,34,36] Thus, carboranes are frequently used to mimic substituted or unsubstituted phenyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ortho -carborane can be thermodynamically converted to meta - and para -carborane at high temperatures [ 24 , 25 ]. Due to the fact of their remarkable stability and hydrophobicity, a growing interest in carboranes for medicinal chemistry applications is becoming evident [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Although the first use of carborane derivatives in boron neutron capture therapy (BNCT) dates back to the 1950s [ 35 ], it was only in 2009 that Hawkins et al showed conclusively that a carborane derivative, namely, a neutral rhenacarborane, can cross the BBB [ 36 ].…”
Section: Introductionmentioning
confidence: 99%